Numerical Method for 1D Poisson-Boltzmann Equation - Rizal Dian Azmi (Indonesian Journal of Mathematics and Applications, 2023)
Poisson-Boltzmann is an equation which is used frequently to model a variety of electrostatic interactions problems in biomolecular computation. A value of atomic energy at the molecular movement becomes a singular value on the PBE. It affects the difficulty of solving this equation both analytically and numerically. In this article, this equation will be solved numerically. In this case, this equation is discretized using finite element method. The resulted system of equation is then solved with inexact backtracking Newton.